PERSEPSI PESERTA DIDIK TENTANG STUDI LANJUT KE PERGURUAN TINGGI - Susanti, Elvi; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
This research is motivated by the lack learners, opinion about study to college, university in MAN Kinali Pasaman Barat, so that. The researcherÂ interested to do the research. Based on first survey that researcher found that Â the lacks, learners opinion about college university. This research aims to describe, 1). Learners perception about selection to join college university, 2). Learners perception about teaching learning process at university.This research is deseriptive qualitative study. Sample of the research are (6) six learners. Data nere collected through interview and documentation study to learners, perception about study to college university. The data analysis technique that used is reduction data, dercribe the data and concluded the data. The result of the research found that, 1). The lack of learners perception about selection to join college university, 2). The lack of learners perception about teaching learning process at university. Based on result of the research, is reconendedn to the learners to use well information that they got from the of school or out of school about college university in order to make easy them join to the college university nith all they knew and understuod about information college university .